2014
DOI: 10.2337/dc14-1432
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Diabetes Incidence: The Framingham Heart Study

Abstract: OBJECTIVEObesity and type 2 diabetes continue to increase in prevalence in the U.S. Whether diabetes incidence continues to increase in recent times is less well documented. We examined trends in diabetes incidence over the previous four decades.RESEARCH DESIGN AND METHODSFramingham Heart Study participants ages 40–55 years and free of diabetes at baseline (n = 4,795; mean age 45.3 years; 51.6% women) were followed for the development of diabetes in the 1970s, 1980s, 1990s, and 2000s. Diabetes was defined as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 15 publications
3
61
1
Order By: Relevance
“…Incidence rates increased between 1991 and 2009 before showing a decreasing tendency between 2009 and 2013 . Several studies have reported that the incidence and prevalence of diabetes in the USA has remained relatively stable in recent years . The increase in prevalence of diagnosed Type 2 diabetes between 2012 and 2013 was less than expected based on the rate of increase observed prior to 2012.…”
Section: Discussionmentioning
confidence: 85%
“…Incidence rates increased between 1991 and 2009 before showing a decreasing tendency between 2009 and 2013 . Several studies have reported that the incidence and prevalence of diabetes in the USA has remained relatively stable in recent years . The increase in prevalence of diagnosed Type 2 diabetes between 2012 and 2013 was less than expected based on the rate of increase observed prior to 2012.…”
Section: Discussionmentioning
confidence: 85%
“…Four comprehensive population‐based surveys were conducted in Jordan during the years 1994, 2004, 2009 and 2017 . These surveys were conducted by the same team of researchers and generally used the same methods.…”
Section: Methodsmentioning
confidence: 99%
“…A 2015 report from the Framingham Heart Study cohort (34) found that the risk of new-onset diabetes was higher in the 2000s compared with the 1970s. However, the authors also found that diabetes incidence did not change significantly in the 2000s compared with the 1990s, despite an increase in mean BMI and despite there being more individuals with obesity in the 2000s.…”
Section: Secular Trends In the Type 2 Diabetes Epidemicmentioning
confidence: 99%